How Nurses Address Mental Health in Underserved Populations - Saleha Abdullah Abdo faqihi; Aminah Mohammed Al Qahtani; Fatimah Taher Saeed masoud; Sheha Hawis Ibrahim; Hayat Saad AL zahrani; Rahmah Ibrahim Alshehri; Jawaher Fahad Alqhtani; Tala Hassan Ali Alshehry; Sultan Saad Abdullah Alyabis; Bander saleh alhakbani; Nooh Safar M Almutairi; Fahad Hamoud Alshammari (International Journal of Medical Toxicology and Legal Medicine, 2024)
Mental health disorders pose a significant burden on underserved populations, who often face barriers to accessing appropriate care and support. Nurses, as frontline healthcare providers, play a crucial role in addressing the mental health needs of these vulnerable communities. This comprehensive paper explores strategies and approaches employed by nurses to promote mental well-being and ensure equitable access to care in underserved populations. The paper delves into the multifaceted role of nurses, including advocacy and health promotion, cultural competence and patient-centered care, interdisciplinary collaboration and community engagement, mental health assessment and early intervention, capacity building and mentorship, and advocacy for policy and resource allocation. By leveraging these approaches, nurses can destigmatize mental health issues, empower individuals and communities, and develop culturally appropriate interventions. Additionally, the paper examines the challenges and barriers faced by nurses, such as limited resources, stigma, language barriers, workforce shortages, and lack of interdisciplinary collaboration. Strategies for overcoming these challenges are discussed, including advocating for increased funding, engaging in cultural competency training, fostering interdisciplinary teamwork, and participating in professional development opportunities. Ethical considerations, including respect for autonomy, beneficence, justice, privacy, and cultural sensitivity, are also addressed, ensuring that nurses' actions align with professional ethical standards and respect the rights and well-being of individuals and communities. Ultimately, by prioritizing mental health in underserved populations and empowering nurses to take a leading role, we can work towards creating more equitable and inclusive healthcare systems that promote overall well-being and improve the lives of vulnerable individuals and communities.